How can Literature be Researched? (2016)
Literature is a field that can be studied with scientific rigor. The researchers of Science Projects, the last stage of the University of Children, have been in charge of analyzing two epistolar works by Gonzalo Arango not only to reconstruct his identity but also his reality.